Expert validation of e-module content on plant importance in mitigating climate change for primary school students - Nordiana Md Khamis; Kamisah Osman; Nurazidawati Mohamad Arsad (Penerbit Universiti Kebangsaan Malaysia, 2025)
Digital learning tools, especially interactive e-modules are transforming climate change education by making complex concepts more accessible to young learners. However, many existing materials lack interactivity and structured validation, limiting their pedagogical impact. This study validates an interactive e-module designed to support primary students’ understanding of plant-climate interactions. Six experts, selected based on their academic qualifications, professional experience (≥10 years), and expertise in science education, climate change, and plant science evaluated the module across seven dimensions: interface design, language use, climate literacy, plant awareness, science process skills, learning theories, and teaching activities. Using a Likert scale and the Content Validity Achievement (CVA) method by Sidek Mohd Noah and Jamaludin Ahmad, the module achieved a CVA score of 90.83%, surpassing the 70% validity benchmark. Expert ratings ranged from 4.17 (SD = 1.60) to 4.83 (SD = 0.41), with an overall mean of 4.54 (SD = 0.65), confirming the module’s quality. Plant awareness (M = 4.70, SD = 0.48), interface design (M = 4.67, SD = 0.55), and science process skills (M = 4.67, SD = 0.71) received the highest ratings. Language use scored lowest (M = 4.17, SD = 1.60) with experts recommending clearer scaffolding of terms like “climate” and “greenhouse” through pre-teaching strategies. These findings confirm the module’s validity and usability while highlighting areas for refinement. Future research should assess the module’s effectiveness and accessibility for students with diverse learning needs, including those with special educational and cognitive differences.